The Moderating Role of Perceived Supervisor Support on the Relationship Between Organizational Dissent and Intention to Leave - KOÇOĞLU SAZKAYA, MERVE (My University, 2022)
The goal of this study is to analyze the relationship between organizational dissent, perceived supervisor support and intention to leave. A review of the literature did not yield many academic studies on the concepts of organizational dissent, perceived supervisor support and intention to leave. Therefore, the originality of this research is that it fills the gap mentioned in the literature. In addition to making a literature review about the concepts mentioned in the study, it is aimed to determine the role of perceived supervisor support on the relationship between organizational dissent and intention to leave. For this purpose, quantitative research was carried out with 313 white-collar employees who were also studying in foundation universities in Istanbul. According to the results of the research, it is determined that there are significant relationships between organizational dissent, perceived supervisor support and intention to leave. Another result of the study is that perceived supervisor support has a moderator role on the relationship between organizational dissent and intention to leave.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Organizational Dissent; Perceived Supervisor Support; Intention to Leave